Exploring Societal Preferences for Energy Sufficiency Measures in Switzerland - Moser, Corinne; Rösch, Andreas; Stauffacher, Michael (Frontiers in Energy Research, 2015)
Many countries are facing a challenging transition toward more sustainable energy systems, which produce more renewables and consume less energy. The latter goal can only be achieved through a combination of efficiency measures and changes in people’s lifestyles and routine behaviors (i.e., sufficiency). While research has shown that acceptance of technical efficiency is relatively high, there is a lack of research on societal preferences for sufficiency measures. However, this is an important prerequisite for designing successful interventions to change behavior. This paper analyses societal preferences for different energy-related behaviors in Switzerland. We use an online choice-based conjoint analysis (N = 150) to examine preferences for behaviors with high technical potentials for energy demand reduction in the following domains: mobility, heating, and food. Each domain comprises different attributes across three levels of sufficiency. Respondents were confronted with trade-off situations evoked through different fictional lifestyles that comprised different combinations of attribute levels. Through a series of trade-off decisions, participants were asked to choose their preferred lifestyle. The results revealed that a vegetarian diet was considered the most critical issue that respondents were unwilling to trade off, followed by distance to workplace and means of transportation. The highest willingness to trade off was found for adjustments in room temperature, holiday travel behaviors, and living space. Participants’ preferences for the most energy-sufficient lifestyles were rather low. However, the study showed that there were lifestyles with substantive energy-saving potentials that were well accepted among respondents. Our study results suggest that the success of energy-sufficiency interventions might depend strongly on the targeted behavior. We speculate that they may face strong resistance (e.g., vegetarian diet). Thus, it seems promising to promote well-balanced lifestyles, rather than extremely energy-sufficient lifestyles, as potential role models for sufficiency.